Marrow Fat and Bone: Review of Clinical Findings - Schwartz, Ann V. (Frontiers in Endocrinology, 2015)
With growing interest in the connection between fat and bone, there has been increased investigation of the relationship with marrow fat in particular. Clinical research has been facilitated by the development of non-invasive methods to measure bone marrow fat content and composition. Studies in different populations using different measurement techniques have established that higher marrow fat is associated with lower bone density and prevalent vertebral fracture. The degree of unsaturation in marrow fat may also affect bone health. Although other fat depots tend to be strongly correlated, marrow fat has a distinct pattern, suggesting separate mechanisms of control. Longitudinal studies are limited, but are crucial to understand the direct and indirect roles of marrow fat as an influence on skeletal health.